Ellagic Acid from Geranium thunbergii and Antimalarial Activity of Korean Medicinal Plants - Hojong Jun; Joon-Hee Han; Min Hong; Fadhila Fitriana; Jadidan Hada Syahada; Wang-Jong Lee; Ernest Mazigo; Johnsy Mary Louis; Van-Truong Nguyen; Seok Ho Cha; Wanjoo Chun; Won Sun Park; et al. (Molecules)
This study investigates the antimalarial potential of extracts and compounds from various plants used in traditional Korean medicine, in response to the increasing resistance of Plasmodium falciparum to standard treatments such as chloroquine and artemisinin. The antimalarial activity screening was conducted on 151 extracts, identifying the top seven candidates, including Geranium thunbergii (50% ethanol and 100% methanol extract), Reynoutria japonica, Amomum villosum (hot water and 50% ethanol extract), Cinnamomum zeylanicum, and Platycodon grandiflorum. Among these, G. thunbergii was identified as the top priority for further analysis due to its high antimalarial activity and high yield of bioactive compounds. The plant extracts were fractionated using ethyl acetate, chloroform, and hot water, and their efficacy against P. falciparum was evaluated through IC50 determination and microscopic analysis. The compounds evaluated included ellagic acid, gallic acid, afzelin, quercetin, and protocatechuic acid. Among the tested compounds, ellagic acid showed the most potent antimalarial activity with an IC50 of 1.60 ± 0.09 µM, followed by gallic acid (39.43 ± 1.48 µM) and afzelin (52.77 ± 1.84 µM). In contrast, quercetin (116.8 ± 3.78 µM) and protocatechuic acid (1.23 ± 0.02 mM) exhibited minimal antimalarial effects. Giemsa staining was employed to visualize parasite morphology and confirmed that ellagic acid is effective in inhibiting growth at the late trophozoite stage. These findings suggest that ellagic acid could serve as a promising lead compound for developing a novel antimalarial agent. This study highlights the importance of exploring plant-based compounds as alternative strategies against drug-resistant malaria. Further investigation into the mechanisms underlying the antimalarial activity of these compounds is necessary to fully validate their therapeutic potential.